Effect of beta-alanine supplementation on 2,000-m rowing-ergometer performance - Ducker, K. J.; Dawson, B.; Wallman, K. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Beta-alanine supplementation has been shown to improve exercise performance in short-term high-intensity efforts. However, whether supplementation with beta-alanine is ergogenic to actual sporting events remains unclear and should be investigated in field testing or race simulations. Purpose: The aim of this study was to assess if beta-alanine supplementation could improve 2,000-m rowing-ergometer performance in well-trained male rowers. Methods: Participants (N = 16) completed duplicate trials (2 × before supplementation and 2 × after supplementation) of a 2,000-m rowing-ergometer race separated by 28 days of either beta-alanine (n =7; 80 mg · kg-1 BM · d-1) or placebo (n = 9; glucose) supplementation. Results: Beta-alanine group (pooled) race times improved by 2.9 ± 4.1 s and placebo group slowed by 1.2 ± 2.9 s, but these results were inconclu- sive for performance enhancement (p = .055, ES = 0.20, smallest worthwhile change = 49% beneficial). Race split times and average power outputs only significantly improved with beta-alanine at the 750-m (time -0.7 s, p = .01, power +3.6%, p = .03) and 1,000-m (time -0.5 s, p = .01, power +2.9%, p = .02) distances. Blood La- and pH postrace values were not different between groups before or after supplementation. Conclusions: Overall, 28 d of beta-alanine supplementation with 80 mg · kg-1 BM · d-1 (~7 g/d) did not conclusively improve 2,000-m rowing-ergometer performance in well-trained rowers.